Oversized nanodiscs for combined structural and functional investigation of multicomponent membrane protein systems - Bozhidar S. Ivanov; Judy Hirst (Scientific Reports)
Abstract Membrane proteins are fundamental to many crucial cellular processes but removing them from their native environment for structural and functional studies creates experimental challenges. Numerous strategies have been developed to replicate native-like membrane environments in vitro for membrane protein research, however, most studies have focused on systems for either structural or functional characterisation, not both together. Here, we apply an in-vivo split intein strategy to produce stable circularised nanodiscs for combined structural and functional analysis of respiratory complex I, using its highly hydrophobic native ubiquinone-10 substrate and an auxiliary ubiquinol oxidase from Trypanosoma brucei brucei. We successfully reconstituted Paracoccus denitrificans complex I into circularised nanodiscs, determined its cryo-EM structure at 3.1 Å resolution and conducted biophysical and biochemical analyses to demonstrate how the ‘oversized’ nanodiscs have space to accommodate both enzymes and substrates to sustain steady-state catalysis. Our work establishes a proof-of-principle for using oversized nanodiscs as an integrated platform for structural and functional interrogation of complex membrane proteins in near-native membrane environments.